Early life stress is associated with default system integrity and emotionality during infancy. (23rd March 2015) - Graham, Alice M.; Pfeifer, Jennifer H.; Fisher, Philip A.; Carpenter, Samuel; Fair, Damien A.
<x xml:space="preserve">Abstract</x> Background Extensive animal research has demonstrated the vulnerability of the brain to early life stress (ELS) with consequences for emotional development and mental health. However, the influence of moderate and common forms of stress on early human brain development is less well‐understood and precisely characterized. To date, most work has focused on severe forms of stress, and/or on brain functioning years after stress exposure. Methods In this report we focused on conflict between parents (interparental conflict), a common and relatively moderate form of ELS that is highly relevant for children's mental health outcomes. We used resting state functional connectivity MRI to examine the coordinated functioning of the infant brain (N = 23; 6–12‐months‐of‐age) in the context of interparental conflict. We focused on the default mode network (DMN) due to its well‐characterized developmental trajectory and implications for mental health. We further examined DMN strength as a mediator between conflict and infants' negative emotionality. Results Higher interparental conflict since birth was associated with infants showing stronger connectivity between two core DMN regions, the posterior cingulate cortex (PCC) and the anterior medial prefrontal cortex (aMPFC). PCC to amygdala connectivity was also increased. Stronger PCC‐aMPFC connectivity mediated between higher conflict and higher negative infant emotionality. Conclusions The developing DMN may be an important marker for effects of ELS with relevance for emotional development and subsequent mental health. Increasing understanding of the associations between common forms of family stress and emerging functional brain networks has potential to inform intervention efforts to improve mental health outcomes.